Evaluasi proyek pengembangan start-up wedding organizer berbasis kemitraan dan kebijakan ekonomi kreatif model countenance stake - Josua, Dian Pertiwi; Siregar, Jenny Sista; Nuridayanti, Nuridayanti; Sutisna, Anan; Suseno, Muchlas; Karlina, Elin (Nur Science Institute, 2025)
The limited systematic evaluation of the effectiveness of partnership-based projects in supporting creative economy policies poses a challenge in developing sustainable entrepreneurship models. This study aims to evaluate the impact and effectiveness of partnership-based Wedding Organizer start-up development projects in supporting national creative economy policies. The evaluation was conducted using Stake's Countenance Model, which includes three main components: antecedents, transactions, and outcomes. The research instrument was developed based on three layers of theory: Grand Theory, Middle Range Theory, and Applied Theory. It was then validated using Aiken's V approach and tested for reliability using Cronbach's Alpha. The study's results indicate that the program has a positive impact on increasing the entrepreneurial capacity of participants, enhancing the effectiveness of partnership-based training, and promoting business sustainability. The program also successfully established a broad business network, directly contributing to local economic growth. These findings provide new insights into the effectiveness of evaluating partnership models within the creative economy ecosystem. This evaluation model can be replicated and adapted for similar programs in other creative sectors to support community-based development policies.